The Alternative Livelihood Practices Engaged by Artisanal Fishers for Household Improvements in Zanzibar Islands - Ali, Subira; Bilame, Odass; Ngusa, Deborah Andrew (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
This paper outlines the alternative livelihood practices used by artisanal fishers for household improvement in five Zanzibar Islands fishing villages: Kizimkazi Dimbani, Chwaka, Unguja Ukuu Kaepwani, Tumbe Mashariki, and Michenzani. The cross-sectional research design was used to collect quantitative data via a questionnaire survey and qualitative data via Focus Group Discussions (FGDs) and key informant interviews. Data were collected from a sample of 333 artisanal fishers drawn from the 1991 population using the Yamane formula. According to the findings of the study, approximately half of the artisanal fishers (53.45%) did not engage in any alternative livelihood practice to support the livelihood of their households and instead relied solely on artisanal fisheries. (23.12%) of the artisanal fishers were farmers, (9.91%) were seaweed farmers, and (5.41% were animal keepers. A small percentage of artisanal fishers (8.11%) engage in petty trade, tourism, and dagaa processing for sale. It is therefore recommended that the respective government, in collaboration with other fisheries stakeholders, establish the sustainability of alternative livelihood opportunities for artisanal fisher communities in order to improve their household livelihoods by diversifying their household survival and reducing the challenge of overexploitation of fishery resources.